Specyfika procesu opracowania strategii małego przedsiębiorstwa - Szatrowa, Jelena W. (Specificity of Strategy Making Process in a Small Company, 2008)
The paper presents the specificity of strategic management in small enterprises, the possibility to use strategic management methods and the reasons for their insufficient implementation in companies.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 372-375